APPLICATION OF ARTIFICIAL INTELLIGENCE (AI) IN TELEVISION INDUSTRY MANAGEMENT STRATEGY USING GROUNDED THEORY ANALYSIS: A CASE STUDY ON TVONE - Dadang Ridwan; Jerry Heikal (Sean Institute, 2023)
The television industry has received many changes over time, especially with ever-increasing technological progress advances. One technology that has limit a significant impacts on this industry is artificial intelligence (AI). the purpose of this research is to understand the application of artificial intelligence (AI) in the television industry management strategy with a case study on tvOne. this study utilized qualitative methods to understand and describe the situation that takes place in the research environment. The sample in this study were five respondents from tvOne's top management. The analysis begins with the coding stage of the data derived from the results of the interviews which limit been transcribed into text using a grounded theory approach. the conclusion of this study is that the opportunity provided by AI for the television industry is content production. Opportunities for implementing AI technology at tvOne, through the integration of AI in content production, are directed at increasing the efficiency and quality of production program by utilizing more sophisticated data analysis and automation. Then, the challenges faced in implementing AI in the television industry areresources. The challenge of implementing AI technology at tvOne is in terms of humanresources and physical resources needed, which includes the necessary technical expertise and the availability of adequate financial resources and infrastructure.